2020
DOI: 10.1186/s12917-020-2246-5
|View full text |Cite
|
Sign up to set email alerts
|

Tylosin exposure reduces the susceptibility of Salmonella Typhimurium to florfenicol and tetracycline

Abstract: Background: Antibiotics exposure has been implicated in the emergence of bacterial strains that are resistant to structurally related or unrelated antibiotics. Tylosin is a macrolide antibiotic that has been administered to treat respiratory pathogenic bacteria in swine. Thus, this study was undertaken to evaluate the impact of exposure to a constant (3 μg/mL) and decreasing concentrations of tylosin on the susceptibility of Salmonella enterica serovar Typhimurium to various antibiotics. Results: S. Typhimuriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Similarly, the induction of ROS was also reported to modulate antibiotic resistance in other pathogenic bacteria. For example, Salmonella Typhimurium was shown to modulate its susceptibility to tetracycline when exposed to a ROS generating macrolide antibiotic, tylosin 27 . Also, in Acinetobacter baumannii, soxR overexpression led to susceptibility to tetracycline 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the induction of ROS was also reported to modulate antibiotic resistance in other pathogenic bacteria. For example, Salmonella Typhimurium was shown to modulate its susceptibility to tetracycline when exposed to a ROS generating macrolide antibiotic, tylosin 27 . Also, in Acinetobacter baumannii, soxR overexpression led to susceptibility to tetracycline 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of tylosin, specifically, was found in 100% (30/30 flocks) of the studied broiler population in Pakistan [ 21 ] and vigorous use of tylosin in broiler production was reported previously [ 20 , 21 ]. Although tylosin is primarily active against Gram-positive bacteria, there are reports of a correlation between exposure to tylosin and a change in susceptibility to other antibacterial drugs and even the emergence of multidrug-resistant strains of enterobacteria [ 22 , 23 ]. Such reports suggest that tylosin susceptibility of resistant strains is variable.…”
Section: Discussionmentioning
confidence: 99%
“…FLR and TET are connected in the graph; these antibiotics are part of the different phenicol and tetracycline classes. A recent study in swine demonstrated that tylosin exposure reduced susceptibility of Salmonella to both drugs ( 40 ). Bacteria exposure to sub-lethal doses of tylosin acquired resistance mechanisms to the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria exposure to sub-lethal doses of tylosin acquired resistance mechanisms to the antibiotic. Exposure to tylosin also resulted in activation of the efflux system and its global regulators, which subsequently increased the MICs of FLR and TET against Salmonella ( 40 ). This finding may explain why FLR and TET are connected in our model, however recent tylosin exposure was not reported in the study population.…”
Section: Discussionmentioning
confidence: 99%